The decision ambiguity problems for the Kazakh language (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2020)
This paper describes the problems of word ambiguity for the Kazakh language, which is one of the languages ​​of the Turkic class. The process of solving the problem of ambiguity for the Kazakh language in the machine translation system for the Kazakh - English and Kazakh - Russian language pairs (and vice versa) is described on the basis of the proposed technology. The proposed technology includes a constraint grammar model and a maximal entropy model for more effectively solving the problem of lexical selection for the Kazakh language. Results are presented by comparing two technologies separately and together.
Keywords: ambiguity, technology, Kazakh language.